Early Exercise Affects Mitochondrial Transcription Factors Expression after Cerebral Ischemia in Rats - Zhang, Qi (Molecular Diversity Preservation International (MDPI), 2012)
Increasing evidence shows that exercise training is neuroprotective after stroke, but the underlying mechanisms are unknown. To clarify this critical issue, the current study investigated the effects of early treadmill exercise on the expression of mitochondrial biogenesis factors. Adult rats were subjected to ischemia induced by middle cerebral artery occlusion followed by reperfusion. Expression of two genes critical for transcriptional regulation of mitochondrial biogenesis, peroxisome proliferator-activated receptor coactivator-1 (PGC-1) and nuclear respiratory factor-1 (NRF-1), were examined by RT-PCR after five days of exercise starting at 24 h after ischemia. Mitochondrial protein cytochrome C oxidase subunit IV (COX IV) was detected by Western blot. Neurological status and cerebral infarct volume were evaluated as indices of brain damage. Treadmill training increased levels of PGC-1 and NRF-1 mRNA, indicating that exercise promotes rehabilitation after ischemia via regulation of mitochondrial biogenesis.